Chinese Version of the mHealth App Usability Questionnaire: Cross-Cultural Adaptation and Validation - Zhao, Shuqing; Cao, Yingjuan; Cao, Heng; Liu, Kao; Lv, Xiaoyan; Zhang, Jinxin; Li, Yuxin; Davidson, Patricia M. (Frontiers in Psychology, 2022)
Background: Mobile health (mHealth) apps have shown the advantages of improving medication compliance, saving time required for diagnosis and treatment, reducing medical expenses, etc. The World Health Organization (WHO) has recommended that mHealth apps should be evaluated prior to their implementation to ensure their accuracy in data analysis. Objective: This study aimed to translate the patient version of the mHealth app usability questionnaire (MAUQ) into Chinese, and to conduct cross-cultural adaptation and reliability and validity tests. Methods: The Brislin’s translation model was used in this study. The cross-cultural adaptation was performed according to experts’ comments and the results of prediction test. The convenience sampling method was utilized to investigate 346 patients who used the “Good Doctor” (“Good Doctor” is the most popular mHealth app in China), and the reliability and validity of the questionnaire were evaluated as well. Results: After translation and cross-cultural adaptation, there were a total of 21 items and 3 dimensions: usability and satisfaction (8 items), system information arrangement (6 items), and efficiency (7 items). The content validity index was determined to be 0.952, indicating that the 21 items used to evaluate the usability of the Chinese version of the MAUQ were well correlated. The Cronbach’s α coefficient of the total questionnaire was 0.912, which revealed that the questionnaire had a high internal consistency. The values of test-retest reliability and split-half reliability of the Chinese version of the MAUQ were 0.869 and 0.701, respectively, representing that the questionnaire had a good stability. Conclusions: The translated questionnaire has good reliability and validity in the context of Chinese culture, and it could be used as a usability testing tool for the patient version of interactive mHealth apps.